Conservative politics and Whig colonial government, 1830–41 - Middleton, A (Oxford University Press, 2021)
This article explores Conservative critiques of Whig colonial rule in the 1830s. Its case is that imperial administrative and constitutional issues occupied a more prominent place in the Tories’ politics of opposition during the ‘decade of Reform’ than historians have assumed. Conservative writers and politicians styled themselves as vigorous defenders of imperial integrity, colonial constitutions, and the colonial church, against the incoherent centralizing and liberalizing innovations of the Whigs. These arguments rested on wider assumptions about the inherent failings of Whiggism, Reformed government and the pernicious global consequences of ‘liberalism’. The article asks how these claims affect our understanding of Conservative politics after the Reform crisis, and reflects on the emergence of new forms of political engagement with issues of colonial government in early nineteenth-century Britain.